The Effect of Institutional Variables on Economic Growth in Iraq - Abdulrahman, Ismael (Journal of Economics and Administrative Sciences, 2025)
The research aims to measure the impact of some institutional variables on the growth of the Iraqi economy during the period (2004-2019). The research problem focused on the following question: Iraq has many natural and human resources, but the country has not achieved growth consistent with the size of these resources. Did institutional factors play a role in disrupting the desired economic growth in Iraq? The research selected two governance variables and three doing business variables prepared by the World Bank. The research used the Vector Error Correction Model, after converting the data to semi-annual data, using the EViews 12 program to estimate the effect of the independent variables (Regulatory Quality, Rule of Law, Cost of business start-up procedures, Registering Property-Cost, and Score Starting Business) on dependent variable represented by the gross domestic product. The research found that the independent variables had a significant impact on the gross domestic product in the long term, and The CointEq1 coefficient indicates that the model tends to adjust slowly in the long term, which means that the Iraqi economy requires more time to return to the stable path. The results in the short run became insignificant and different from the results in the long run.